Prevention of elder abuse in domestic setting: Islamic approach - Asiah, Bidin; Kamaliah, Salleh; Noor ‘Ashikin, Hamid; Noraida, Harun (2019)
Elder abuse is a malicious act prevalent in almost all over the world. In searching for solutions, many theories have been introduced and initiated. Despite numerous approaches and research carried out to find ways to prevent elder abuse case, only few studies have examined the prevention of elder abuse from an Islamic perspective. The aims of this article are to discuss the status of the elderly and the concept of family life in Islam. The article further explores the concept of prevention of elder abuse in domestic setting from an Islamic perspective. This article applies a qualitative approach. The verses from al-Quran and the Sunnah/ hadith of the Prophet (PBUH) were gathered and analysed using content analysis. Based on the analysis, this article found that Islam has laid down a very clear provisions pertaining to managing the family relationship by prescribing every individual member in a family the specific rights and obligations. The strict obedience and adherence to these provisions can prevent the problem of abuse of the elderly parents by family members.